Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
g) \(x^5-3x^4+3x^3-x^2=x^2\left(x^3-3x^2+3x-1\right)=x^2\left(x-1\right)^3\)
f) \(x^2-25-2xy+y^2=\left(x^2-2xy+y^2\right)-25=\left(x-y\right)^2-5^2=\left(x-y-5\right)\left(x-y+5\right)\)
e) \(16x^3+54y^3=2\left(8x^3+27y^3\right)=2\left[\left(2x\right)^3+\left(3y\right)^3\right]=2\left(2x+3y\right)\left(4x^2-6xy+9y^2\right)\)
d) \(3y^2-3z^2+3x^2+6xy=3\left(x^2+2xy+y^2-z^2\right)=3\left[\left(x+y\right)^2-z^2\right]=3\left(x+y+z\right)\left(x+y-z\right)\)
Answer:
\(5x^2-10xy+5y^2-20z^2\)
\(=5.\left(x^2-2xy+y^2-4z^2\right)\)
\(=5.[\left(x+y\right)^2-\left(2z\right)^2]\)
\(=5.\left(x+y-2z\right).\left(x+y+2z\right)\)
\(16x-5x^2-3\)
\(=\left(-5x^2+15x\right)+\left(x-3\right)\)
\(=-5x.\left(x-3\right)+\left(x-3\right)\)
\(=\left(1-5x\right).\left(x-3\right)\)
\(x^2-5x+5y-y^2\)
\(=(x-y).(x+y)-5.(x-y)\)
\(=(x-y).(x+y-5)\)
\(3x^2-6xy+3y^2-12z^2\)
\(=3.(x^2-2xy+y^2-4z^2)\)
\(=3[\left(x-y\right)^2-\left(2z\right)^2]\)
\(=3.(x-y-2z).(x-y+2z)\)
\(x^2+4x+3\)
\(=(x^2+x)+(3x+3)\)
\(=x.(x+1)+3.(x+1)\)
\(=(x+1).(x+3)\)
\((x^2+1)^2-4x^2\)
\(=(x^2-2x+1).(x^2+2x+1)\)
\(=(x-1)^2.(x+1)^2\)
\(x^2-4x-5\)
\(=(x^2+x)-(5x+5)\)
\(=x.(x+1)-5.(x+1)\)
\(=(x-5).(x+1)\)
Trả lời:
a, \(-xy.\left(x^2+2xy-3\right)=-x^3y-2x^2y^2+3xy\)
b, \(\left(12x^6y^5-3x^3y^4+4x^2y\right):6x^2y\)
\(=12x^6y^5:6x^2y^2-3x^3y^4:6x^2y+4x^2y+6x^2y\)
\(=2x^4y^3-\frac{1}{2}xy^3+\frac{2}{3}\)
a.\(\left(-xy\right)\left(x^2+2xy-3\right)=-x^3y-2x^2y^2+6xy\)
b.\(\left(12x^6y^5-3x^3y^4+4x^2y\right):6x^2y=2x^4y^4-\frac{1}{2}xy^3+\frac{2}{3}\)
Trả lời:
a, 3x2y - 6xy = 3xy ( x - 2 )
b, x2 - y2 - 9x + 9y
= ( x2 - y2 ) - ( 9x - 9y )
= ( x - y )( x + y ) - 9 ( x - y )
= ( x - y )( x + y - 9 )
c, x3 - 6x2 - y2x + 9x
= x ( x2 - 6x - y2 + 9 )
= x [ ( x2 - 6x + 9 ) - y2 ]
= x [ ( x - 3 )2 - y2 ]
= x ( x - 3 - y )( x - 3 + y )
3x2y - 6xy = 3xy( x - 2 )
x2 - y2 - 9x + 9y = ( x - y )( x + y ) - 9( x - y ) = ( x - y )( x + y - 9 )
x3 - 6x2 - y2x + 9x = x( x2 - 6x - y2 + 9 ) = x[ ( x - 3 )2 - y2 ] = x( x - y - 3 )( x + y - 3 )
a) \(x^3+2x^2y+xy^2-4xz^2=x\left(x^2+2xy+y^2-4z^2\right)=x\left[\left(x+y\right)^2-\left(2z\right)^2\right]\)
\(=x\left(x+y-2z\right)\left(x+y+2z\right)\)
b)\(-8x^3+12x^2y-6xy^2+y^3=y^3+3.y.\left(2x\right)^2-3.y^2.2x-\left(2x\right)^3\)\(=\left(y-2x\right)^3\)
c)\(6x^2+7x-5=2x\left(3x+5\right)-\left(3x+5\right)=\left(3x+5\right)\left(2x-1\right)\)
d)\(x^4+64y^4=\left(x^2\right)^2+2.x^2.8y^2+\left(8y^2\right)^2-16x^2y^2=\left(x^2+8y^2\right)-\left(4xy\right)^2\)
\(=\left(x^2+8y^2-4xy\right)\left(x^2+8y^2+4xy\right)\)
e)\(x\left(2-x\right)-x+2=x\left(2-x\right)+\left(2-x\right)=\left(2-x\right)\left(x+1\right)\)
f)\(2x^2+3x-2=2x\left(x+2\right)-\left(x+2\right)=\left(x+2\right)\left(2x-1\right)\)
h)\(3x^2-6xy+3y^2-12z^2=3\left(x^2-2xy+y^2-4z^2\right)=3\left[\left(x-y\right)^2-\left(2z\right)^2\right]\)
\(=3\left(x-y-2z\right)\left(x-y+2z\right)\)
g)\(x^3-3x^2-9x+27=x^2\left(x-3\right)-9\left(x-3\right)=\left(x-3\right)\left(x^2-9\right)\)\(=\left(x-3\right)^2\left(x+3\right)\)
B2: \(x^3-5x=0\Rightarrow x\left(x^2-5\right)=0\Rightarrow\orbr{\begin{cases}x=0\\x^2-5=0\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x^2=5\end{cases}\Rightarrow\orbr{\begin{cases}x=0\\x=\pm\sqrt{5}\end{cases}}}\)\(\Rightarrow\orbr{\begin{cases}x=0\\x^2=5\end{cases}}\Rightarrow\orbr{\begin{cases}x=0\\\orbr{\begin{cases}x=\sqrt{5}\\x=-\sqrt{5}\end{cases}}\end{cases}}\)
a, \(3x\left(x-2\right)-2x+4=3x\left(x-2\right)-2\left(x-2\right)=\left(3x-2\right)\left(x-2\right)\)
b, \(x^2+2xy+y^2-9z^2=\left(x+y\right)^2-\left(3z\right)^2=\left(x+y-3z\right)\left(x+y+3z\right)\)
c, \(x^2+xy-3x-3y=x\left(x+y\right)-3\left(x+y\right)=\left(x-3\right)\left(x+y\right)\)
d, \(x^2-4xy-9+4y^2=\left(x+2y\right)^2-3^2=\left(x+2y-3\right)\left(x+2y+3\right)\)
e, \(x^2-5x-xy+5y=x\left(x-y\right)-5\left(x-y\right)=\left(x-5\right)\left(x-y\right)\)
g, \(x^2+2xy-9+y^2=\left(x+y\right)^2-3^2=\left(x+y-3\right)\left(x+y+3\right)\)
h, \(7x\left(x-2021\right)-x+2021=7x\left(x-2021\right)-\left(x-2021\right)=\left(7x-1\right)\left(x-2021\right)\)
i, \(\left(3x+1\right)^2-\left(2x-3\right)^2=\left(3x+1-2x+3\right)\left(3x+1+2x-3\right)=\left(x+4\right)\left(5x-2\right)\)
c) \(3x\left(x-2\right)-2x+4\)
\(3x\left(x-2\right)-2\left(x-2\right)\)
\(\left(x-2\right)\left(3x-2\right)\)
d) \(x^2+2xy+y^2-9z^2\)
\(\left(x+y\right)^2-\left(3z\right)^2\)
\(\left(x-y-3z\right)\left(x-y+3z\right)\)
e)\(x^2+xy-3x-3y\)
\(x\left(x+y\right)-3\left(x+y\right)\)
\(\left(x+y\right)\left(x-3\right)\)
f) \(x^2-4xy-9+4y^2\)
\(\left(x-2y\right)^2-3^2\)
\(\left(x-2y-3\right)\left(x-2y+3\right)\)
g) \(x^2-5x-xy+5y\)
\(x\left(x-5\right)-y\left(x-5\right)\)
\(\left(x-5\right)\left(x-y\right)\)
h) \(x^2+2xy+y^2-9\)
\(\left(x+y\right)^2-3^2\)
\(\left(x-y-3\right)\left(x-y+3\right)\)
i) \(7x\left(x-2021\right)-x+2021\)
\(\left(x-2021\right)\left(7x-1\right)\)
j) \(\left(3x+1\right)^2-\left(2x-3\right)^2\)
\(\left(3x+1-2x+3\right)\left(3x+1+2x-3\right)\)
\(\left(x+4\right)\left(5x-2\right)\)